2017
DOI: 10.1007/s10936-017-9501-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Efficiency in Highly Proficient Bilinguals and Simultaneous Interpreters: Evidence from Language Switching and Stroop Tasks

Abstract: The present behavioral study aimed to examine the impact of language control expertise on two domain-general control processes, i.e. active inhibition of competing representations and overcoming of inhibition. We compared how Simultaneous Interpreters (SI) and Highly Proficient Bilinguals-two groups assumed to differ in language control capacity-performed executive tasks involving specific inhibition processes. In Experiment 1 (language decision task), both active and overcoming of inhibition processes are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 83 publications
0
16
1
Order By: Relevance
“…A first shortcoming of this study is that we did not compare cognitive abilities and executive functions between the two groups, rendering it difficult to relate white matter differences to specific psychological functions. Even though it is not yet clear whether interpreting training might promote cognitive functions more strongly than multilingualism per se (Aparicio et al, 2017;Henrard and Van Daele, 2017;van der Linden et al, 2018), we cannot exclude that some between-group differences in cognitive functioning might have influenced the results. A second shortcoming of our work is that we did not explicitly test the language competence of the participants but only required that they were able to fluently speak the foreign languages in a conversational context (i.e., based on selfreport).…”
Section: Limitationsmentioning
confidence: 89%
“…A first shortcoming of this study is that we did not compare cognitive abilities and executive functions between the two groups, rendering it difficult to relate white matter differences to specific psychological functions. Even though it is not yet clear whether interpreting training might promote cognitive functions more strongly than multilingualism per se (Aparicio et al, 2017;Henrard and Van Daele, 2017;van der Linden et al, 2018), we cannot exclude that some between-group differences in cognitive functioning might have influenced the results. A second shortcoming of our work is that we did not explicitly test the language competence of the participants but only required that they were able to fluently speak the foreign languages in a conversational context (i.e., based on selfreport).…”
Section: Limitationsmentioning
confidence: 89%
“…Admittedly, some studies have failed to report whether their IS or PSI samples were matched for L2 proficiency/experience with UMs (e.g., Bajo et al, 2000; Darò, 1989; Fabbro et al, 1991; Hiltunen et al, 2016; Szarkowska et al, 2018; Tzou et al, 2012). Although interpreter advantages in those cases may well be reflecting the impact of higher language competence, most reports have effectively ruled out this confound (e.g., Aparicio et al, 2017; Babcock & Vallesi, 2017; Elmer & Kühnis, 2016; Hervais-Adelman et al, 2015, 2017; Morales et al, 2015; Santilli et al, 2018; Signorelli et al, 2012; Van de Putte et al, 2018; Yudes et al, 2011, 2013), suggesting that such effects could actually be specifically driven by experience in this particular activity.…”
Section: Discussion: On the Adaptability Of Neurocognitive Systems Inmentioning
confidence: 99%
“…Indeed, Santilli et al (2018) found that PSIs had shorter response times than UMs in both translation directions despite being matched in L2 competence, age of acquisition, years of study, and weekly exposure. Also, PSIs proved more accurate and faster than UMs with similar language proficiency at detecting whether serially presented words belonged to their L1 or L2 (Aparicio, Heidlmayr & Isel, 2017). Thus, sustained engagement in interlingual reformulation by PSIs may optimize cross-linguistic processing and language identification skills, even beyond the impact of L2 proficiency.…”
Section: Evidence From Interpreting Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in that study the late bilingual group consisted of students enrolled in a professional school for interpreters, who may have already possessed considerable expertise in simultaneous language access. Simultaneous interpreters appear to control language differently from other bilinguals, as reflected by reduced and symmetric language switch costs (Morales, Padilla, Gómez-Ariza, & Bajo, 2015;Babcock & Vallesi, 2017;Ibáñez, Macizo, & Bajo, 2010;Aparicio, Heidlmayr, & Isel, 2017). In addition, the small sample size of Costa et al (2006) may have reduced their study's statistical power.…”
Section: Introductionmentioning
confidence: 99%